The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3727/096368914x681739
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Antagonist TG-0054 Mobilizes Mesenchymal Stem Cells, Attenuates Inflammation, and Preserves Cardiac Systolic Function in a Porcine Model of Myocardial Infarction

Abstract: Interaction between chemokine stromal cell-derived factor 1 and the CXC chemokine receptor 4 (CXCR4) governs the sequestration and mobilization of bone marrow stem cells. We investigated the therapeutic potential of TG-0054, a novel CXCR4 antagonist, in attenuating cardiac dysfunction after myocardial infarction (MI). In miniature pigs (minipigs), TG-0054 mobilized CD34(+)CXCR4(+), CD133(+)CXCR4(+), and CD271(+)CXCR4(+) cells into peripheral circulation. After isolation and expansion, TG-0054-mobilized CD271(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…For example, TG-0054 has recently been investigated for its therapeutic potential in an animal model of myocardial infarction. It could be shown that the administration of TG-0054 after induction of myocardial infarction leads to a mobilization of mesenchymal stem cells, preventing left ventricular dysfunction and causing a decrease in inflammatory cytokine levels ( 246 ). A phase II clinical trial to assess the pharmacokinetics and safety of TG-0054 for the mobilization of stem cells in patients with multiple myeloma, non-Hodgkin lymphoma, or Hodgkin disease has been completed by the end of 2014; however, the results have not been published to date (clinical trials NCT01458288).…”
Section: Development and Clinical Use Of Cxcr4 Antagonistsmentioning
confidence: 99%
“…For example, TG-0054 has recently been investigated for its therapeutic potential in an animal model of myocardial infarction. It could be shown that the administration of TG-0054 after induction of myocardial infarction leads to a mobilization of mesenchymal stem cells, preventing left ventricular dysfunction and causing a decrease in inflammatory cytokine levels ( 246 ). A phase II clinical trial to assess the pharmacokinetics and safety of TG-0054 for the mobilization of stem cells in patients with multiple myeloma, non-Hodgkin lymphoma, or Hodgkin disease has been completed by the end of 2014; however, the results have not been published to date (clinical trials NCT01458288).…”
Section: Development and Clinical Use Of Cxcr4 Antagonistsmentioning
confidence: 99%
“…Consequently, if this situation also happens in humans with nut allergies, it would have significant clinical implications in both developing novel treatments (e.g., novel cardiac mast cell stabilizers, antagonist to IL-6/Chemokines/their receptors identified here; novel methods to deliver these antidotes locally within the heart) and improving the diagnosis of near fatal reactions with novel cardiac function monitoring methods (e.g., via developing novel methods to monitor cardiac tissue levels of specific mediators and analyze elevated levels of mediators identified in this study in the blood and/or using non-invasive methods) (Santone et al 2008;Hsu et al 2014;Guttmann et al 2014). Furthermore, a nut induced systemic allergic reaction may have to be dealt similar to acute myocardial infarction ('heart attack').…”
Section: Discussionmentioning
confidence: 98%
“…Single or short‐term intermittent treatment with CXCR4 antagonists improved cardiac recovery by augmenting the mobilization and recruitment of stem/progenitor cells from the bone marrow to the injured area after MI . On the contrary, continuous treatment with Plerixafor TM inhibited this protective effect .…”
Section: Therapeutic Potential For Intervention With Cxcl12/cxcr4 Axismentioning
confidence: 99%
“…Chemical structures of purine-based CXCR4 antagonists 118-125 4.13 TG-0054 (Burixafor) TG-0054 (Burixafor, 132) is another nonpeptide-like CXC4 antagonist in the clinical development by Taigen. With the completion of the phase I trial, it has progressed into a phase II study for HSC transplantation in NHL and MM patients.Moreover, other CXCR4-meidated therapeutic areas, such as age-related macular degeneration and MI, are also under investigation 165,272,273. TG-0054 (Burixafor) in its phase II trial was reported to meet with the primary endpoint for PBSCT via a single IV infusion, which may provide more advantages over multiple daily subcutaneous (SC) doses of AMD3100.…”
mentioning
confidence: 99%